Invited presentation: Nanoscale sensor devices with diamond color centers - Nelz, Richard; Opaluch, Oliver; Hochstetter, Axel; Rani, Dipti; Oshnik, Nimba; Neu, Elke (Optics InfoBase Conference Papers, 2020)
We summarize novel fabrication techniques and novel materials for single crystal diamond nanostructures containing shallow nitrogen vacancy color centers and their scalability. We demonstrate near-field energy transfer between NV centers and 2D materials and multi-functional sensing capabilities of NV centers.
CRIS-Team Scopus Importer:2023-03-27